Patient benefits and cost arrangement in JKN in Indonesia and learnings from Japan: A literature review - Tuanku Banang Rabbani Imsyaamru; Rizky Khaeran; Rizwandy Wasir (Indonesian Journal of Health Science, 2026)
Universal Health Coverage emphasizes the need for effective financial protection in addition to expanding health insurance coverage. The National Health Insurance (JKN) has successfully increased healthcare coverage in Indonesia, but still faces challenges in structuring benefit packages and patient costs. Study aims to synthesize scientific evidence on the design of benefit packages and patient cost mechanisms within JKN and examine lessons learned from the Japanese healthcare system. The study employed literature review design, examining scientific articles from 2016–2025 obtained from PubMed, Google Scholar, and credible health organization sources. Articles meeting the inclusion criteria were analyzed using thematic analysis based on the themes of benefit structuring, cost sharing, and financial protection. The study results indicate, although the JKN benefit package formally supports coverage expansion, a gap remains between benefits and effective access, characterized by high unmet need and indirect costs borne by participants. Furthermore, patient cost structuring within JKN remains implicit and poorly integrated. Lessons learned from Japan suggest that strengthening primary care and cost sharing based on economic capacity can improve efficiency without reducing access to services. Therefore, it is necessary to strengthen the primary service benefit package and improve the cost sharing design to be fairer and more transparent.